ANALYSIS OF THE USE OF MALE AND FEMALE LANGUAGE IN POETRY WRITING BY STUDENTS AT MUHAMMADIYAH UNIVERSITY OF SIDENRENG RAPPANG - T, Wirdaningsih; Yusman,; Lanta, Jumiati; Kasau, M. Nurzin R. (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to determine the differences in language use between men and women in poetry writing by students at Muhammadiyah University of Sidenreng Rappang. This study applies a descriptive approach with qualitative methods. This study utilizes two approaches to obtain data, namely data reduction and data presentation. The research data is in the form of text in the form of: words, phrases, sentences, in poetry written by students. The data sources used in this study include poetry from semester 3 and 5 students of the 2023/2024 academic year, totaling 30 poems, 15 poems by female students and 15 poems by male students written in college assignments. Data reduction is carried out through in-depth observation to collect data, as well as recording, classifying, and categorizing data relevant to the problem formulation. Based on this research, it can be concluded that in poetry writing by students at Muhammadiyah University of Sidenreng Rappang, the most frequently used language is color words. The use of language is dominated by women, as seen from the use of color wordwhich are found more often than men.